The importance of Primary Health Care in the detection and treatment of depressive symptoms in the elderly (Research, Society and Development, 2021)
The expressive increase in the number of elderly people is a global event, which has been occurring steadily. Data show that this population will approach 2 billion people by 2050. Associated with this growth, depressive symptoms and depression, properly speaking, reveal concern about an incident epidemic, mainly in the age group of the elderly, who usually neglect symptoms with belief that they are inherent to the natural aging process. The present study is an integrative literature review and aimed to demonstrate the importance of primary health care in detecting depressive symptoms in the elderly, to know the problems related to the symptoms, to identify the best instrument for early detection of the problem and to describe the therapies used in the elderly with depressive symptoms. The search was carried out in the electronic databases SCIELO, LILACS and BIREME, including works published between 2011 and 2019, in Portuguese. The selection of studies, data extraction and validation were carried out independently by two authors, obtaining a sample of 37 articles. It was found, through the data analyzed, the main methods used to screen for depressive symptoms, the most associated comorbidities reported in the literature and the main methods addressed for treatment. Thus, it was possible to systematically structure the most recent reports of the problem in primary health care and lay the ground for elucidation, choice and possible standardization of screening methods.